The Influence Of Human Resource Development On Employee Performance In The Globalization Era Of Pt Elva - Ndruru, Hardijan (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
This study aimed to examine the effect of human resource development on employee performance in the PT.ELVA Globalization era. Based on the results examined at PT. Based on the number of respondents, ELVA is expected to have 50 researchers. The number of respondents was 50 people, and employees were mostly 20-29 years old, 26 people and 15 people aged 30-39 years, and nine people aged 40-49 years. The sex of all male respondents was 50 people. The education level of employees is where two people have a bachelor's degree, 44 people have a high school education, and four people have junior high school education—using data analysis techniques in the form of SPSS: validity and reliability tests and definitive assumption tests, Partial Test (t-test), F Test (Simultaneous Test), and Coefficient of Determination. Based on the results of a study of 50 respondents, the variables of education and training, non-training activities, promotion, and motivation significantly affect employee performance. Simultaneously, the variables of education and training, non-training activities, promotion, and motivation significantly affect employee performance. The variables of education and training, non-training activities, promotion, and motivation are 0.664. 66.4% of education and training, non-training activities, promotion, and motivation simultaneously affect employee performance. At the same time, some (33.6%) are explained by other variables that are not included as variables in the study.